Sappho fr. 44.12 and Virgil, Aeneid 4.173 - Metcalf, C (Cambridge University Press, 2023)
This note shows that Virgil’s description of Fama at Aeneid 4.173 is substantially indebted, in phrasing and context, to Sappho fr. 44.12.